دور القضاء الدولي في تطوير إلزامية مبادئ القانون الدولي الانساني (محكمة العدل الدولية إنموذجا) - تركي, عادل احمد (Journal of Legal Sciences, 2017)
We had, in this research, the role of international justice in the mandatory principles of international humanitarian law development (ICJ model), where divided by the two sections: the first, outlining the direction of the international character of the judiciary on the Convention and the principles of customary international humanitarian law.The second section, which handled the position of international justice in the peremptory norms of international humanitarian law of nature.In conclusion we dealt with the most important conclusions we reached in this regard, and some of the necessary recommendations in this area.